Prospective, randomized, multicenter Food and Drug Administration investigational device exemption study of lumbar total disc replacement with the CHARITÉ artificial disc versus lumbar fusion: Five-year follow-up - Guyer, Richard D.; McAfee, Paul C.; Banco, Robert J.; Bitan, Fabian D.; Cappuccino, Andrew; Geisler, Fred H.; Hochschuler, Stephen H.; Holt, Richard T.; Jenis, Louis G.; Majd, Mohamed E.; Regan, John J.; Tromanhauser, Scott G.; et al. (The spine journal, 2009)
The CHARITÉ artificial disc, a lumbar spinal arthroplasty device, was approved by the United States Food and Drug Administration in 2004 based on two-year safety and effectiveness data from a multicenter, prospective, randomized investigational device exemption (IDE) study. No long-term, randomized, prospective study on the CHARITÉ disc or any other artificial disc has been published to date. The purpose of this study was to compare the safety and effectiveness at the five-year follow-up time point of lumbar total disc replacement using the CHARITÉ artificial disc (DePuy Spine, Raynham, MA) with that of anterior lumbar interbody fusion (ALIF) with BAK cages and iliac crest autograft, for the treatment of single-level degenerative disc disease from L4 to S1, unresponsive to nonoperative treatment. Randomized controlled trial—five-year follow-up. Ninety CHARITÉ patients and 43 BAK patients. Self-reported measures: visual analog scale (VAS); validated Oswestry disability index (ODI version 1.0); Short-Form 36 Questionnaire, and patient satisfaction. Physiologic measures: radiographic range of motion, disc height, and segmental translation. Functional measures: work status. Of the 375 subjects enrolled in the CHARITÉ IDE trial, 277 were eligible for the five-year study and 160 patients thereof completed the five-year follow-up. The completers included 133 randomized patients. Overall success was defined as improvement≥15 pts in ODI vs. baseline, no device failure, absence of major complications, and maintenance or improvement of neurological status. Additional clinical outcomes included an ODI questionnaire as well as VAS, SF-36, and patient satisfaction surveys. Work status was tracked for all patients. Safety assessments included occurrence and severity of adverse events and device failures. Radiographic analyses such as index- and adjacent-level range of motion, segmental translation, disc height, and longitudinal ossification were also carried out. Overall success was 57.8% in the CHARITÉ group vs. 51.2% in the BAK group (Blackwelder's test: p=0.0359, Δ=0.10). In addition, mean changes from baseline for ODI (CHARITÉ: −24.0 pts vs. BAK: −27.5 pts), VAS pain scores (CHARITÉ: −38.7 vs. BAK: −40.0), and SF-36 questionnaires (SF-36 Physical Component Scores [PCS]: CHARITÉ: 12.6 pts vs. BAK: 12.3 pts) were similar across groups. In patient satisfaction surveys, 78% of CHARITÉ patients were satisfied vs. 72% of BAK patients. A total of 65.6% patients in the CHARITÉ group vs. 46.5% patients in the BAK group were employed full-time. This difference was statistically significant (p=0.0403). Long-term disability was recorded for 8.0% of CHARITÉ patients and 20.9% of BAK patients, a difference that was also statistically significant (p=0.0441). Additional index-level surgery was performed in 7.7% of CHARITÉ patients and 16.3% of BAK patients. Radiographic findings included operative and adjacent-level range of motion (ROM), intervertebral disc height and segmental translation. At the five-year follow-up, the mean ROM at the index level was 6.0° for CHARITÉ patients and 1.0° for BAK patients. Changes in disc height were also similar for both CHARITÉ and BAK patients (0.7 mm for both groups, p=0.9827). Segmental translation was 0.4 and 0.8 mm in patients implanted with CHARITÉ at L4–L5 vs. L5–S1, respectively, and 0.1 mm in BAK patients. The results of this five-year, prospective, randomized multicenter study are consistent with the two-year reports of noninferiority of CHARITÉ artificial disc vs. ALIF with BAK and iliac crest autograft. No statistical differences were found in clinical outcomes between groups. In addition, CHARITÉ patients reached a statistically greater rate of part- and full-time employment and a statistically lower rate of long-term disability, compared with BAK patients. Radiographically, the ROMs at index- and adjacent levels were not statistically different from those observed at two-years postsurgery.